2017
DOI: 10.4240/wjgs.v9.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Perforated peptic ulcer - an update

Abstract: Peptic ulcer disease (PUD) affects 4 million people worldwide annually. The incidence of PUD has been estimated at around 1.5% to 3%. Perforated peptic ulcer (PPU) is a serious complication of PUD and patients with PPU often present with acute abdomen that carries high risk for morbidity and mortality. The lifetime prevalence of perforation in patients with PUD is about 5%. PPU carries a mortality ranging from 1.3% to 20%. Thirty-day mortality rate reaching 20% and 90-d mortality rate of up to 30% have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
193
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(245 citation statements)
references
References 119 publications
2
193
2
14
Order By: Relevance
“…Patients were divided into two groups of 20 in test and 8 in control group. The median VAS Score of burning sensation in abdomen in control group was 8 [8,8] on base line (0 day) and 3 [2,5] on 45th day, whereas in test group the median score was 8 [7,8] on baseline (0 day) and 0[0,3] on 45th day. When the median VAS Score of two groups were compared statistically using Friedman test with Dunn pair comparison test for intra-group comparison and Krushkall Wallis for inter group comparison, it was found that the median VAS Score at 30th and 45th day in control group was reduced significantly (P<0.01) when compared with median VAS Score0th day of control group.…”
Section: Resultmentioning
confidence: 99%
“…Patients were divided into two groups of 20 in test and 8 in control group. The median VAS Score of burning sensation in abdomen in control group was 8 [8,8] on base line (0 day) and 3 [2,5] on 45th day, whereas in test group the median score was 8 [7,8] on baseline (0 day) and 0[0,3] on 45th day. When the median VAS Score of two groups were compared statistically using Friedman test with Dunn pair comparison test for intra-group comparison and Krushkall Wallis for inter group comparison, it was found that the median VAS Score at 30th and 45th day in control group was reduced significantly (P<0.01) when compared with median VAS Score0th day of control group.…”
Section: Resultmentioning
confidence: 99%
“…[6,11,12,5] Buck and colleagues on the other hand expressed the meagre ability of Boey score in predicting mortality and morbidity status. [13] Their multicentre study also stated that the ASA score, and sepsis score were not able to provide convincing results in prognostication of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 601 patients and including 62 patients treated with gastric resection, they noted that outcomes of patients treated with gastric resection were found to be more inferior when compared to omental patch repair with mortality risk of 24.2% (8). Some of the reasons for this outcome may include:…”
Section: Omentoplasty In Perforated Peptic Ulcer Surgery: Is It Stillmentioning
confidence: 99%
“…The narrative on this treatment over a century later has not changed much. It still consists of primary closure of the perforation by sutures and a convenient tag of adjacent omentum on top of this (7,8). Although this may sound very simplistic, PPU still remains a life threatening condition with a high mortality of up to 40% which cannot be underestimated (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation